Synopsis: Enhancing smallholder farmers’ profitability through increased crop commercialization in Rwanda - Mugabo, Serge; Warner, James (International Food Policy Research Institute, 2024)
This study analyzes the costs, returns, and profitability of smallholder agriculture in Rwanda using a gross margin approach (definitions are provided below) and reveals that over 80 percent of farmers generate positive gross economic margins. However, only around 40 percent achieve positive gross marketing margins from crop sales. This difference is directly attributable to the fact that two-thirds of production is directly consumed by households. The analysis further identifies that farm households allocate about 80 percent of their total crop input expenditures to fertilizer, seed, and hired labor, while the remaining expenses associated with fixed production costs that are almost exclusively related to land rental costs.